2012
DOI: 10.1097/mat.0b013e318271badb
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Response to a Simplified Venovenous Perfusion-Induced Systemic Hyperthermia System

Abstract: Our original venovenous perfusion-induced systemic hyperthermia (vv-PISH) system appeared to significantly improve lung cancer patient survival, but was too complex with numerous dialysis problems. We tested a simplified vv-PISH circuit that includes the AvalonElite double lumen cannula, a modified heat exchanger, water heater/cooler, and a centrifugal pump. The purpose of this study was to evaluate this simplified vv-PISH system (without hemodialyzer) and to investigate the physiological response to whole bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The heated blood is well mixed with unheated venous blood through the pulmonary circulation and is distributed to the systemic circulation by the heart, which results in homogenous delivery of systemic hyperthermia. 1415 Fast heating can also be achieved with the vv-PISH system, which enhances cancer cell kill. 19 Thus, vv-PISH rapidly and homogeneously delivers a therapeutic dose, meeting the requirements needed for efficacious hyperthermic cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The heated blood is well mixed with unheated venous blood through the pulmonary circulation and is distributed to the systemic circulation by the heart, which results in homogenous delivery of systemic hyperthermia. 1415 Fast heating can also be achieved with the vv-PISH system, which enhances cancer cell kill. 19 Thus, vv-PISH rapidly and homogeneously delivers a therapeutic dose, meeting the requirements needed for efficacious hyperthermic cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these improvements in the vv-PISH circuit, significant pulmonary hypertension developed during the heating phase, resulting in circulatory instability. 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 For practical clinical application of hyperthermia, we recently developed a simplified vv-PISH system and management protocol. 20-21 In this paper, we report the results of our preclinical Good Laboratory Practice (GLP) investigation which was designed to prove the safety and accuracy of the simplified vv-PISH system in a 5 day sheep survival study. Our results showed that an accurate dose of therapeutic hyperthermia was safely delivered to sheep with no hyperthermia-related complications.…”
Section: Introductionmentioning
confidence: 99%